2007
DOI: 10.1261/rna.569407
|View full text |Cite
|
Sign up to set email alerts
|

Widespread use of poly(A) tail length control to accentuate expression of the yeast transcriptome

Abstract: Control of poly(A) tail length can affect translation and stability of eukaryotic mRNAs. Although well established for individual cases, it was not known to what extent this type of adjustable gene control is used to shape expression of eukaryotic transcriptomes. Here we report on microarray-based measurements of mRNA poly(A) tail lengths and association with the poly(A)-binding protein Pab1 in S. cerevisiae, revealing extensive correlation between tail length and other physical and functional mRNA characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
158
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(171 citation statements)
references
References 76 publications
(105 reference statements)
9
158
2
2
Order By: Relevance
“…This approach may elucidate some novel translational controls required for efficient translation of mRNAs encoding cell cycle regulators, which, as discussed above, in some cases require specialized translational initiation factors owing to their long and complex UTRs. Moreover, recent genome-wide profiling experiments of poly(A) tail lengths performed in transcriptionally active mitotically dividing cells have been a step forward in delineating the role of 3 0 UTRs in regulation of archetypal cell cycle progression [78,122,123]. This work suggests that polyadenylation status of mRNAs could be implicated in the regulation of archetypal cell cycle progression [78,122].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…This approach may elucidate some novel translational controls required for efficient translation of mRNAs encoding cell cycle regulators, which, as discussed above, in some cases require specialized translational initiation factors owing to their long and complex UTRs. Moreover, recent genome-wide profiling experiments of poly(A) tail lengths performed in transcriptionally active mitotically dividing cells have been a step forward in delineating the role of 3 0 UTRs in regulation of archetypal cell cycle progression [78,122,123]. This work suggests that polyadenylation status of mRNAs could be implicated in the regulation of archetypal cell cycle progression [78,122].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 97%
“…Microarray-based analyses of mRNA polyadenylation state uncovered widespread use of mRNA-specific poly(A) tail length control in the S. cerevisiae and Schizosaccharomyces pombe transcriptomes (Beilharz and Preiss 2007;Lackner et al 2007). Of note here, many mRNAs encoding cell cycle, cell polarity, and morphogenesis-related functions including septin assembly, were found to be present with mostly short oligo(A) tails in nonsynchronized, exponentially growing wild-type (wt) cell cultures.…”
mentioning
confidence: 90%
“…Of note here, many mRNAs encoding cell cycle, cell polarity, and morphogenesis-related functions including septin assembly, were found to be present with mostly short oligo(A) tails in nonsynchronized, exponentially growing wild-type (wt) cell cultures. These data suggested that rapid deadenylation by Ccr4-Pop2-NOT of such ''short-tailed'' mRNAs serves as a mechanism to restrict their translation to a tight time window during the cell cycle (Beilharz and Preiss 2007). Thus, even though the Ccr4-Pop2-NOT deadenylase shortens the poly(A) tails of virtually all mRNAs (Parker and Song 2004;Woolstencroft et al 2006;Beilharz and Preiss 2007;Goldstrohm and Wickens 2008), its effects on the group of ''short-tailed'' mRNAs are particularly critical for cell function, and their deregulation in deadenylase mutant cells is therefore likely to contribute to observable phenotypes.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…56 However, the fate of hyperadenylated transcripts is unclear. These hyperadenylated transcripts may simply be more abundant 57 and therefore translated more often, leading to elevated levels of their encoded proteins. Alternatively, hyperadenylated transcripts could be removed from cells via the RNA degradation machinery.…”
Section: Mutations In the Conserved Znf Pab Zc3h14 Are Linked To Nsmentioning
confidence: 99%